Day 7 Embryos Change the Proteomics and Exosomal Micro-RNAs Content of Bovine Uterine Fluid: Involvement of Innate Immune Functions - Kusama, Kazuya; Rashid, Mohammad B.; Kowsar, Rasoul; Marey, Mohamed A.; Talukder, Anup K.; Nagaoka, Kentaro; Shimada, Masayuki; Khatib, Hasan; Imakawa, Kazuhiko; Miyamoto, Akio (Frontiers in Genetics, 2021)
This study aimed to characterize proteins and exosomal microRNAs (miRNAs) in the uterine flushings (UF) of cows associated with Day 7 pregnancy using the embryo donor cows of the embryo transfer program. Superovulated cows either were inseminated (AI cows) or remained uninseminated (Ctrl cows). UF was collected on D7 in the presence of multiple embryos (AI cows) or without embryos (Ctrl cows) and subjected to Isobaric Tags for Relative and Absolute Quantification (iTRAQ) protein analysis. A total of 336 proteins were identified, of which 260 proteins were more than two-fold higher in AI cows than Ctrl cows. Gene ontology analysis revealed that many differentially expressed proteins were involved in “neutrophil-related” and “extracellular vesicular exosome-related” terms. In silico analysis of proteins with higher concentrations in the UF of AI identified 18 uniquely expressed proteins. Exosomes were isolated from the UF, from which RNA was subjected to miRNA-seq, identifying 37 miRNAs. Of these, three miRNAs were lower, and six miRNAs were higher in the UF of AI cows than those of Ctrl ones. The principal component analysis (PCA) displayed a close association in miRNA and protein between bta-miR-29a, bta-miR-199b, SUGT1, and PPID. In addition, the receiver operating characteristic (ROC) curve analysis showed that SUGT1 was the best predictor for the presence of embryos in the uterus. These findings suggest that the presence of multiple D7 embryos in the uterus can lead to significant changes in the protein composition and exosomal miRNA contents of UF, which could mediate innate immunological interactions between the pre-hatching embryo and the uterus in cows.